Strategy Of User Education Program Development At Dinas Perpustakaan Dan Kearsipan Kota Medan - Hesti, Yola May; Batubara, Abdul Karim; Jamil, Khoirul (International Journal of Cultural and Social Science, 2022)
This study discusses the User Education Program Development Strategy at the Medan City Government Library and Archives Service. The purpose of this study was to find out how the Strategy for Development of User Education Programs at the Medan City Government Library and Archives Service was. This research method uses a qualitative descriptive approach. Using data collection techniques through interviews, observation and documentation. The informants in this study were librarians at the Medan City Government Library and Archives Service. The results showed that there were several user education development strategies implemented by the Medan City Government Library and Archives Service in dealing with the obstacles that occurred. This activity aims to keep users from getting user education from the library.